Dokumentation i et nyt lys - Riis, Nina Ventzel (Hikuin, 2011)
Building documentation in a new perspective By Nina Ventzel Riis The article discusses the field of Architectural records and documentations and what efforts should be done to optimize the quality of future documentations. Through the last approximately 300 years we have had the same aim when recording the architectural heritage. We work hard to make the perfect drawing and in recent years digital technology has helped us to reach our goals with more and more details in less time. But who says that the perfect drawing is the only true product of a thorough building inventory? The drawing has many advantages but it cannot contain all possible information. There is a growing interest in the fact that atmosphere is an important part of the architectural heritage, but nevertheless it is never to find in any of our architectural records. Why? Is it because it does not belong in an objective document qua the intangible and, some would say, impossible form it has? Or is it because we have no methods or tools to record these kinds of values? By involving Michel Foucault’s view on implementing the diversity in history, the article takes up the fact that the field of documentation needs new methods to reach new knowledge.